ATP Release from Chemotherapy-Treated Dying Leukemia Cells Elicits an Immune Suppressive Effect by Increasing Regulatory T Cells and Tolerogenic Dendritic Cells - Lecciso, Mariangela; Ocadlikova, Darina; Sangaletti, Sabina; Trabanelli, Sara; De Marchi, Elena; Orioli, Elisa; Pegoraro, Anna; Portararo, Paola; Jandus, Camilla; Bontadini, Andrea; Redavid, Annarita; Salvestrini, Valentina; et al. (Frontiers in Immunology, 2017)
ABSTRACT Chemotherapy-induced immunogenic cell death can favor dendritic cell cross-priming of tumor-associated antigens for T cell activation thanks to the release of damage-associated molecular patterns, including ATP. Here, we tested the hypothesis that in acute myeloid leukemia, ATP release, along with its well-known immune stimulatory effect, may also contribute to the generation of an immune suppressive microenvironment. In a cohort of acute myeloid leukemia patients, undergoing combined daunorubicin and cytarabine chemotherapy, a population of T regulatory cells with suppressive phenotype, expressing the immune checkpoint programmed cell death protein 1, was significantly increased. Moving from these results, initial in vitro data showed that daunorubicin was more effective than cytarabine in modulating dendritic cell function towards T regulatory cells induction and such difference was correlated with the higher capacity of daunorubicin to induce ATP release from treated acute myeloid leukemia cells. Dendritic cells cultured with daunorubicin-treated acute myeloid leukemia cells up-regulated indoleamine 2,3-dioxygenase 1 (IDO1), which induced anti-leukemia T regulatory cells. These data were confirmed in vivo as daunorubicin-treated mice show an increase in extracellular ATP levels with increased number of T regulatory cells, expressing programmed cell death protein 1 and IDO1+CD39+ dendritic cells. Notably, daunorubicin failed to induce T regulatory cells and tolerogenic dendritic cells in mice lacking the ATP-receptor P2X7. Our data indicate that ATP release from chemotherapy-treated dying cells contributes to create an immune suppressive microenvironment in acute myeloid leukemia.